31. KEBIJAKAN PEMERINTAH INDONESIA DAN KOREA SELATAN DALAM MENANGANI TKI OVERSTAY DI KOREA SELATAN - Siva Anggita Maharani; Tri Cahyo Utomo; Shary Charlotte Pattipelohy (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
This research aims to describe Indonesia and South Korea policies in tackling overstayedIndonesian migrant workers in South Korea. Both countries have signed MoU on theSending Indonesian Workers to the Republic of Korea under Employment Permit Systemsince 2004. Indonesia and South Korea implement several policies through either bilateralpolicy and unilateral policy to resolve the problem. This research uses qualitative as amethod and neoliberalism as a theory to explain policies that released by Indonesia andSouth Korea. Those policies should be maximizing both parties absolute gain as mentionedin the neoliberalism theory. Indonesia had released four main policies. South Koreapolicies stand for general term of overstayed foreign worker. As conclusion, the policiesneed a strong supervision on their implementation for efficiency increment.